The secret life of memorials : through the memory lens of the Australian South Sea Islanders - Mitchell, Julie Kaye, (Archaeopress archaeology., 2019)
Focusing on the Australian South Sea Islander minority community this volume employs a variety of theoretical arguments in order to contribute a new method for comprehending the many interleaving aspects of memory spaces, and should be of interest to heritage professionals, local councils and governing bodies, and members of the general public.